Didactic component in the management model for educative projects in teaching training majors - Maribel Ferrer-Vicente; Alfredo Rebollar-Morote (Maestro y Sociedad, 2016)
The educative project is designed considering the pedagogical, sociological and educational foundations for leading the process of initial and ongoing formation in an increasing tendence in training for solving the problems of their professional, so that the didactic component of the educational management, strategically orients transformations throughout the educational community. Problem solving is understood from a position that reveals the transition from a student from the learning and preparing him/herself to learn to learn, learning to teach how to learn and learning to self-assessing. The challenge of the managers of the educative project is to lead it to the desired state: a professional who learn to solve problems.